Changes in training load, running performance, lower body power and biochemical characteristics of back players throughout a professional Rugby Union season - Dubois, R.; Paillard, T.; McGrath, D.; Chamari, K.; Maurelli, O.; Polly, S.; Prioux, J. (Journal of Human Sport & Exercise, 2017)
The aim of this study was to observe and quantify changes in training load (TL), running performance, lower body power and biochemical characteristics of professional rugby union back players over an entire season. Eight professional players (age: 25.8 ± 4.6 y) participated in this study. Session-RPE (S-RPE) and microtechnologies (GPS) were used for assessing training load (TL). During the season, running performance was monitored using the YoYo Recovery Test Level-2 (YYRT2) and lower body power performance using the drop jump (DJ) test. Changes in hematological, endocrine and muscle damage parameters were examined through 3 blood samples taken at separate times throughout the season. TL progressively and significantly (p < 0.001) decreased throughout the season particularly due to the decrease in the training volume. The last blood sample of the season revealed a significant (p < 0.001) increase in hematological parameters and a significant increase (p < 0.01) in cortisol blood concentration without change in the testosterone/cortisol ratio. No significant change in YYRT2 performance was observed over the season, while DJ test performance was significantly lower during the first 2 blocks of the season compared to other blocks. The training volume showed a significant negative correlation with DJ-test performances (TD: r = -0.49 and S-RPE: r = -0.40, p < 0.001). Although there was a decrease in training volume throughout the season, there was no significant changes in running performance. Furthermore, lower body power production showed a significant increase in particular during the last part of the season.